Efforts to Improve Student Learning Outcomes on the Material Emulating the Struggle of the Prophet Muhammad, the Event of the Conquest of Mecca and the Farewell Pilgrimage at SD Negeri 152981 Tukka 1A - Sibuea, Erawati; Idawati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students' learning outcomes in the material